2021
DOI: 10.21203/rs.3.rs-678096/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

East Meets West in the Western Carpathians: Contact Zone Between Alpine and Carpathian Caddisfly Lineages Evidenced by COI Barcodes

Abstract: European mountains are important areas regarding biodiversity of the continent, and they also harbour diverse freshwater fauna, which is critically endangered in terms of the current species extinction. However, sufficient knowledge of this valuable part of European biota is no longer possible without molecular data. This study focuses on the genetic diversity and distribution patterns of the classical representative of the mountain freshwater fauna, caddisfly Rhyacophila tristis, in the Western Carpathians. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…It has been demonstrated that Quaternary climate change has had a huge influence on many species' distributions and population structures [4,15]. Our analyses (i.e., mismatch distributions, Tajima's D, Fu's Fs, network of haplotypes, BEAST analysis and BSP) all indicated a recent expansion, and also showed that the divergence time of C. chinensis populations mainly occurred in Quaternary glaciations.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…It has been demonstrated that Quaternary climate change has had a huge influence on many species' distributions and population structures [4,15]. Our analyses (i.e., mismatch distributions, Tajima's D, Fu's Fs, network of haplotypes, BEAST analysis and BSP) all indicated a recent expansion, and also showed that the divergence time of C. chinensis populations mainly occurred in Quaternary glaciations.…”
Section: Discussionmentioning
confidence: 55%
“…For example, the Mississippi River and the Appalachian Mountains in eastern North America caused genetic differentiation among populations of some taxa [9][10][11][12][13][14]. Geographic isolation has resulted in strong genetic differences between populations such as the caddisfly, in western and Eastern Europe [15]. China has a vast territory, a wide span of latitudes, and provides a wide diversity of climates.…”
Section: Introductionmentioning
confidence: 99%